Direct synthesis of graphene 3D-coated Cu nanosilks network for antioxidant transparent conducting electrode1. Issue 24 (28th June 2015) - Xu, Hongmei; Wang, Huachun; Wu, Chenping; Lin, Na; Soomro, Abdul Majid; Guo, Huizhang; Liu, Chuan; Yang, Xiaodong; Wu, Yaping; Cai, Duanjun; Kang, JunYong
<x xml:space="preserve">Abstract</x> Cu@graphene nanosilk network achieves high transparency, high flexibility, low resistance and antioxidance.